Decentralisation Processes in Ukraine: Dilemmas of Democratisation and National Security. Public policy and administration. - Sabadash, Nataliia; Kruglashov, Anatoliy (Public Policy and Administration. 2022, Vol. 21, Nr. 1, p. 22-37, 2022)
Ukraine has been facing unprecedented challenges since 2014. A Revolution of dignity makes Ukraine turn closer to the EU and NATO, while ongoing and expanded Russian aggression threatens the very existence of Ukrainian statehood. One of the key directions of making Ukraine resilient to threats and challenges is the decentralisation process. It aims at making the government and public administration in Ukraine more democratic, transparent and efficient, open to public concerns and the needs and expectations of local communities.The article proposes analytical approaches towards the decentralisation process taking into account theimperative of democratisation and security challenges that Ukraine has been dealing with. The authors consider both dimensions of the national regional policy and self-government reforms, proposing a balanced vision on their advantages and disadvantages, as well as pointing out key problems that should be attended by the government. The process of decentralisation means a lot for Ukraine to make its statehood stronger and more secure vis-a-vis threats the country is facingnow.
Keywords: Ukraine, security, decentralisation, reforms of self-government, local democracy